2020
DOI: 10.33503/jp.jok.v3i2.622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of The Effects Of Glucose And Coffee Toward Blood Glucose Levels And Muscular Endurance After Eccentric Activity

Abstract: The study aims to know the effects of glucose and coffe on blood glucose levels and muscular endurance after eccentric activity. The reseach subjects of badminton athletes PB MBC Malang fell 27 male athletes. Design (Randomized group pretest and posttest disign) is the research design chosen for this study. Glucose given before students do eccentric sports with a dose of 10 grams/70 kg BW, coffee given at a dose of 10grams/70kg BW. Eccentrie activity  done by pulling up 2 sets, 7 repettions and 30 seconds inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This research is in line with [9] consuming drinks that contain carbohydrates or drinks that contain sugar can improve performance when exercising. Sari [13] in his research on soccer athletes in Samarinda found that drinking coffee can have an effect on muscle endurance before exercising theoretically caffeine is a major component of coffee that has an effect on human muscles, caffeine can improve muscle performance and inhibit muscle fatigue, but when compared with the provision of glucose before exercise, the effect of glucose on muscle power is far better than the provision of coffee before exercise [14] drinking coffee before exercising can have an effect on increasing V02Max endurance [15]. Giving dates juice before exercising can increase endurance V02Max [16].…”
Section: Introductionmentioning
confidence: 99%
“…This research is in line with [9] consuming drinks that contain carbohydrates or drinks that contain sugar can improve performance when exercising. Sari [13] in his research on soccer athletes in Samarinda found that drinking coffee can have an effect on muscle endurance before exercising theoretically caffeine is a major component of coffee that has an effect on human muscles, caffeine can improve muscle performance and inhibit muscle fatigue, but when compared with the provision of glucose before exercise, the effect of glucose on muscle power is far better than the provision of coffee before exercise [14] drinking coffee before exercising can have an effect on increasing V02Max endurance [15]. Giving dates juice before exercising can increase endurance V02Max [16].…”
Section: Introductionmentioning
confidence: 99%